The effect of additional shading utilizing agriphotovoltaic structures on the visual qualities and metabolites of broccoli - Moon, Hyeon-Woo; Ku, Kang-Mo (Frontiers in Plant Science, 2023)
Agriphotovoltaic (APV) systems allow the simultaneous production of crops and electricity in the same land area. Since the reduction of yield caused by APV systems is important for food security, studies to improve the yield have been conducted steadily. However, there have been limited data on the appearance, quality, and metabolomic changes of crops. Therefore, in this study, we evaluated the visual qualities and metabolites as well as the yield of broccoli grown using an APV system during fall season. In addition, additional shading treatment was performed, and the same qualities were evaluated. In the spring season, an additional cultivar that does not express anthocyanins was cultivated. Glucosinolate content was more sensitive to the seasonal environment and the type of cultivar than it was to treatment type. The additional shading treatment had a positive effect on the visual qualities of anthocyanin-expressing broccoli cultivar regardless of the season, and we observed that even a cultivar that does not express anthocyanins can be greener. Regardless of cultivar, higher chlorophyll content was detected in broccoli florets with additional shading treatment under the APV system. In addition, reduced anthocyanin content was observed (6.1 mg g -1 DW; about 20% of that obtained on open-field). Aspartic acid content was enhanced upon additional shading treatment. Pathway analysis revealed changes in anthocyanin, alanine, aspartic acid, and glutamic acid metabolism. Overall, our findings suggests that it is possible to produce crops with better visual qualities by utilizing APV systems.